PERAN PANTI ASUHAN DALAM PEMBERDAYAAN ANAK ASUH DI PANTI ASUHAN NAHDIYAT KELURAHAN MARICAYA SELATAN KECAMATAN MAMAJANG KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This journal was created aiming to describe the main problem of this research, namely how the role of the orphanage in empowering foster children at the Nahdiyat Orphanage, South Maricaya Village, Mamajang District, Makassar City. This study uses a qualitative research type with a sociological approach and an empowerment approach located at the Nahdiyat Orphanage. The primary data source in this research is the management and chairman of the Nahdiyat Foundation as a key informant named Ir. Taheriati, and one administrator named Ayu Azhariyah later served as additional informants for 4 coaches named Ahmad Dani, Hendra Setiawan, Ahmad Akbar, and Fatma, and 4 foster children aged 15-18 years named, Ilham, Salam Syam, Masrura, and Sarita. While the secondary data sources are library materials, literature, previous research, books, sites on the internet related to the research carried out, and so on. Data collection methods used are observation, interviews, and documentation. Data processing techniques and data analysis were carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study stated that the role of the board in increasing the empowerment of foster children was instilling religious values ​​in foster children from childhood, providing role models for foster children, teaching good morals and manners to foster children, forms of empowerment and realization of empowerment applied at the Nahdiyat Orphanage.